Gender Difference in Perceiving The Characteristics of Good and Effective EFL Teachers - Ida Ayu Putu Nila Rusmayanti; Luh Putu Artini; Luh Gede Eka Wahyuni (Journal on Education, 2024)
This study investigated the different perceptions of female and male students about the characteristics of good and effective EFL teachers—the subjects of this research from 3 classes of Grade 8 students in SMP Negeri 1 Banjar. A total of 97 students were assigned to fill out a self-ranked questionnaire and 20 students (10 male and 10 female) were randomly selected to take part in a Focus Group Discussion. The results revealed there are differences in the perceptions of female and male students about the characteristics of good and effective teachers. For good EFL teachers, male students show a preference for an English teacher who remembers students' names, while female students do not think that remembering students' names is important. Apart from differences in perception between female and male students, both female and male students perceive care about all students as the most important value of good EFL teachers. Similarly, there were some differences between female and male students’ perceptions about effective EFL teachers. Females more than males agreed that effective EFL teachers provide activities that can check student progress. At the same time, males agreed that the use of a language level appropriate to the student's abilities defines the characteristics of an effective EFL teacher.